Tests and Proofs c - Brucker, Achim D.; Julliand, Jacques; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Test and Proofs, TAP 2012, held in Prague, Czech Republic, in May/June 2012, as part of the TOOLS 2012 Federated Conferences. The 9 revised full papers presented together with 2 invited papers, 4 short papers and one tutorial were carefully reviewed and selected from 29 submissions. The papers are devoted to the convergence of tests and proofs for developing novel techniques and application that support engineers in building secure, safe, and reliable systems. Among the topics covered are model-based testing; scenario-based testing; complex data structure generation; and the validation of protocols and libraries.
Keywords: Computer science; Software engineering; Logic design; Computer simulation; Computer Science; Software Engineering; Programming Techniques; Logics and Meanings of Programs; Mathematical Logic and Formal Languages; Programming Languages, Compilers, Interpreters; Simulation and Modeling